Information control and competence: participant experience of public participation in EIA for proposed mining projects in Queensland. Issue 3 (3rd July 2021) - Meissner, Katie; Everingham, J.A.
ABSTRACT: Public participation is embedded within requirements for Environmental Impact Assessment (EIA) in Australia and many other countries. Although the widespread requirements for public participation have been criticised as rhetorical, it is deemed to have significant symbolic significance. The use of public participation to gather multiple perspectives expresses an intent to improve environmental decision-making and respond to increasing demand for a role in decisions that affect people's homes, livelihoods, and communities. This research examines participant experience of public participation in the EIA processes undertaken for four proposed coal mining developments close to the small, remote cattle grazing community of Alpha, in Queensland's Galilee Basin in the central west of the state. Participant experience is examined through the lens of competence in environmental decision-making, which asserts that, for public participation to be competent, participants need access to information and its interpretations. Participants in 25 semi-structured interviews described two major flaws in public participation in relation to the proposed projects: proponent control of project information, and the government's 'hands-off' approach.